Automatic warehouse modelling and simulation. (18th July 2012) - Guasch, A.; Piera, M.A.; Figueras, J.
The Newspaper Production/Distribution Problem (NDP) involves a perishable good. Newspaper publishers cannot print the news sections of newspapers in advance, as they must be up to date. Additionally, delivery must be completed before morning commuting starts in metropolitan areas. Therefore, delivery delays at the printing plant are not acceptable, as they cause significant disturbances to the distribution chain. In this paper, we analyse the impact of using a second transelevator on the performance of a printing plant's automatic warehouse with the aim to avoid delivery delays to the printing press.